(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Hydrazinolysis of ethyl-5-morpholin-4-yl-1-(1H-pyrrol-1-yl)-6,7,8,9-tetrahydrothieno[2,3-c]iso- quinoline-2-carboxylate afforded the corresponding carbo- hydrazide which upon condensation with aromatic aldehydes, acetyl acetone and/ or carbon disulfide gave N- arylidinecarbohydrazide, dimethylpyrazolyl methanone, [1,3,4]oxadiazole-2-thiol and its ethyl ester derivatives respectively. Diazotization of the carbohydrazide with nitrous acid afforded the corresponding carboazide which was used for synthesis of carbamates and substituted carboxamides. Boiling of the carboazide in dry xylene afforded the pyrazinone compound which was used for synthesis of other heterocycles containing pyrrolopyrazinothinoisoquinoline moeity.